Stochastic Model of Operating Modes of a Group of Artesian Wellsin Water Supply Systems - Тевяшев, А. Д.; Матвієнко, О. І.; Никитенко, Г. В. (ХНУРЕ, 2020)
This work is about development of a stochastic model and a method of modeling of the operating modes of a group of artesian wells.
Keywords: artesian well; water supply system; optimization; stochastic model